Socio-economic analysis of motorboat operators plying the Caticlan-Boracay route. - Delos Reyes, Mary Jane
This study is about the socio-economic conditions of the motorboat operators plying the Caticlan-Boracay route. With the use of simple random sampling method, forty-four (44) respondents were interviewed for a period of one and a half months (April 15 ? June 3, 1997). The motorboat operators have an average age of 30 years old, majority of them are married. Thirty four percent of the respondents was able to finish at least secondary education. A large percentage (93%) lived in a one-story house. Eighty percent (80%) of them owned their home and home-lots. Electricity was the primary source of light by sixty-six (66%) of the respondents. Water supply usually come from piped deep well. Approximately eighty one (81%) of the households have water-sealed toilet facilities. Most households (89%) dispose their garbage by burning. Wood is commonly used as fuel because of its cheap value. Most of the households owned wall clock, radio/cassette, bicycle, electric fan, motorcycle, TV sets, and flat iron for household conveniences. Forty (40) households belonged to nuclear family and four (4) households belonged to the extended type of family. The respondents were classified as operators and owner-operators. Operating expenses include fuel, repair and maintenance, license, association fees, and registration fees. An average-sized motorboat can accommodate twenty (20) commuters. Working days vary according to the schedules of motorboats per week. The average trips of a motorboat are eight (8) trips a day. Operators used crude oil for fuel. Fifteen respondents considered motorboat operation as their main source of income. Others depend on salaries and livelihood projects in the acquisition of the household income. The average monthly income of the operators? households amounted to P8,154.72. The mean expenditures of each household accounted to P6,978.18. Food acquired the highest outlay with a mean of P3,028.02 per month. Other outlays include grocery items (P2,254.28), beverages and tobacco (P688.66), education (P429.73), clothing (P240.41), health (P105.74), electricity (P1373.760), transportation (P168.92), housing repairs and maintenance (P56.87), contributions (during special occasions) (P152.16). With the aim to assess the prevailing socio-economic conditions of the operators? households, the 1994 Poverty Estimates were utilized as baseline in the estimation of food and poverty thresholds. The figures illustrate that 55% belong to core poor families based on the national average while on the regional average, core poor families comprised 45% of the total families. The poverty level of the motorboat operators? households amounted to P6,696.64 which indicates that they belong to the poor sector of our society because they fall below the defined poverty line on the regional (8,197) and national (8,825) averages. The multiple linear regression analysis was employed in analyzing the relationships between the quantitative variables. The postulated regression model was found out to be highly significant with an F-observed value equal to 24.001 which is greater than the F-critical value with 3 and 40 degrees of freedom. There were seven (7) independent variables identified to explain the level of income of the operators. Three (3) factors were found out to be significant and that includes capacity of boat (X2), working days per week (X4), and number of crew members (X5). The value of R2 is .906 and exhibits that 90.6% of the total variations is explained by the significant independent variables.